A Mask to be Visible? – Language and Authenticity in Ocean Vuong’s Novel On Earth We’re Briefly Gorgeous - Waselowsky, Betty (Satura, 2022)
A mask is an object that covers up what’s underneath and gives the person who wears it a different appearance to the outside world. If we approach language as a mask, does it merely serve to help the speaker assimilate into a culture, or is it more than that? Language in Ocean Vuong’s novel On Earth We’re Briefly Gorgeous is particularly relevant, as the novel is written in English, not the Vietnamese passed down to the protagonist Little Dog by his mother Rose.